Interrupted Inferior Vena Cava with Hemiazygos Continuation in an Adult with a Persistent Left Superior Vena Cava and Left Single Coronary Artery: A Case Report - Kim, Yeo Jin; Kwon, Se Hwan; Ahn, Sung-Eun; Kim, Soo-Joong; Shin, Jong Soo; Oh, Joo Hyeong (Journal of the Korean Society of Radiology, 2016)
A 50-year-old woman was referred to our institution for medical screening due to an incidental finding on abdominal ultrasonography. She underwent chest, abdomen and cardiac multi-detector computed tomography (MDCT). Her MDCT revealed absence of the hepatic segment of the inferior vena cava (IVC), with hemiazygos continuation and a left single coronary artery. The dilated hemiazygos vein drained directly into the persistent left superior vena cava (SVC). Herein, we reported a very rare case combining an incidentally found interrupted IVC with hemiazygos vein continuation, persistent left SVC and a left single coronary artery diagnosed by MDCT.